THE BIRTH OF THE AVANT-GARDE: THE 1980S AS A TURNING POINT IN THE HISTORY OF CHINESE POETRY - Krenz, Joanna (Porównania, 2019)
The paper sketches the history of Chinese poetry in the 1980s, taking into account transformations of implicit and explicit poetics, social-political context, and interpersonal and institutional relations between various actors on the dynamically changing poetry scene of the Middle Kingdom. It is in the 1980s that the structures of the Chinese contemporary poetry scene were substantially shaped, and the most consequential ruptures began to appear. In the following two decades, these were to result in deepening conflicts between authors which culminated in a famous national poetry conference in the Panfeng Hotel in Beijing in 1999. Their legacy has carried until today.